The Synergy of Competency Strategy of Islamic Education Teacher to Improve the Quality of Education and Character of Students in Millenial Era - Yoespie Amirullah (Educan : Jurnal Pendidikan Islam, 2020)
This article aims to form "Synergy Islamic Education teacher strategy in improving the quality of education and moral character of students in the Millennial era". Diera Millenial, eras eroded by the current of globalization. As a result education is displaced by negative values that come from western culture. Moreover, mental decline in the nature, character and character that is less in accordance with social behavior. therefore, Islamic Religious Education is a good step to improve student character. The role of the PAI teacher in handling student cases in the Millennial era is a scope which is in accordance with the PAI teacher method. Both in teaching methods and education quality standards. In this case Total Quality Management (TQM) is a good step in shaping management within the school, family and community environment. Therefore character education in the millennial era is very much needed in facing the challenges of globalization. The result is in improving the quality of education and character of students in the Millennial Era. Then there is a contribution in improving integrated quality management (TQM) that can be done for the progress of madrasas, including: 1) Quality strategy planning with regard to: a) Vision b) Mission c) Objectives d) Long-term Institutional Strategy e) Supervision and evaluation 2) Improvement The quality of the process includes: a) Curriculum b) The learning process 3) Improving the quality of Human Resources (HR) 4) Improving the Environmental Quality Improving the Quality of Services 5) Improving the Quality of Outpout.